Obstructive Sleep Apnea as an Independent Stroke Risk Factor: Possible Mechanisms - Godoy, Jaime; Mellado, Patricio; Tapia, Jorge; Santin, Julia (Current Molecular Medicine, 2009)
Obstructive Sleep Apnea (OSA) is a prevalent disease that has emerged as a new cerebrovascular disease (CVD) risk factor, which is independent of its association to hypertension, age and other known conditions that increase CVD. The mechanisms involved in this relation are most likely induced by the periodic hypoxia/ reoxygenation that characteristically occurs in OSA, which results in oxidative stress, endothelial dysfunction and activation of the inflammatory cascade, all of which favor atherogenesis. Numerous markers of these changes have been reported in OSA patients, including increased circulating free radicals, increased lipid peroxidation, decreased antioxidant capacity, elevation of tumor necrosis factor and interleukines, increased levels of proinflammatory nuclear transcription factor kappa B, decreased circulating nitric oxide, elevation of vascular adhesion molecules and vascular endothelial growth factor. In addition, several authors have described that Continuous Positive Airway Pressure, the standard OSA therapy, reverts these abnormalities. Further research is needed in order to better clarify the complex mechanisms that underlie the relation between OSA, atherogenesis and CVD which most likely will have significant clinical impact.
Keywords: Obstructive Sleep Apnea (OSA)